2013
DOI: 10.1371/journal.pone.0066892
|View full text |Cite
|
Sign up to set email alerts
|

p21-Activated Kinase 3 (PAK3) Is an AP-1 Regulated Gene Contributing to Actin Organisation and Migration of Transformed Fibroblasts

Abstract: Activating Protein 1 (AP-1) plays a vital role in cell proliferation, differentiation and apoptosis. While de-regulation of AP-1 has been linked to many cancers, little is known regarding its downstream transcriptional targets that associate with cellular transformation. Previous studies identified PAK3, a serine/threonine kinase, as a potential AP-1 target gene. PAK3 has been implicated in a variety of pathological disorders and over-expression of other PAK-family members has been linked to cancer. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Although direct evidence proving that PAK2 and PAK3 are implicated in the regulation of the ovarian GC proliferation is lacking, PAK2 has been shown to bind and phosphorylate caspase-7, which fractionally decreases its activity and thereby inhibits cellular apoptosis in human breast carcinoma tissue 41 . Furthermore, PAK3 expression is required for cell migration and actin organization in transformed fibroblasts 42 . The over-expression of the PAK3 protein has been associated with the proliferation of mouse corticotrophs 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Although direct evidence proving that PAK2 and PAK3 are implicated in the regulation of the ovarian GC proliferation is lacking, PAK2 has been shown to bind and phosphorylate caspase-7, which fractionally decreases its activity and thereby inhibits cellular apoptosis in human breast carcinoma tissue 41 . Furthermore, PAK3 expression is required for cell migration and actin organization in transformed fibroblasts 42 . The over-expression of the PAK3 protein has been associated with the proliferation of mouse corticotrophs 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PAK2 and PAK4 has also been shown to be regulated by miRNAs 1113 . Finally, PAK3 transcription was recently reported to be regulated by AP-1 14 . Given reports that expression of certain PAK genes is increased by oncogenic signals 15 , we can expect that future work will uncover additional regulators of PAK transcription or translation that are relevant to cancer.…”
Section: Upregulation Of Pak In Cancermentioning
confidence: 99%
“…Conversely, PAK inhibition leads to reduced migratory and less invasive potential of cancer cells [9399]. …”
Section: P-21 Activated Kinasesmentioning
confidence: 99%
“…It has also been reported that the promotion of invasion through extracellular matrix degradation can be mediated by PAK-induced secretion of matrix metalloproteinases MMP-1, MMP-2, MMP-3 and MMP-9 [ 77 , 92 , 93 ]. Conversely, PAK inhibition leads to reduced migratory and less invasive potential of cancer cells [ 93 99 ].…”
Section: P-21 Activated Kinasesmentioning
confidence: 99%